Liu Shen Wan regulates the SPHK1/S1P axis to ameliorate influenza-induced inflammation via integrated network pharmacology and lipidomics - Lei, Biao; Liu, Zhenyang; Xie, Peifang; Li, Xuanxuan; Cui, Zhanyu; Chen, Ruihan; Liu, Bin; Chen, Shihua; Li, Yaxin; Liang, Min; Liang, Hao; Li, Ai; et al. (Frontiers in Immunology, 2026)
BackgroundLiu Shen Wan (LSW) can modulate sphingolipid metabolism, which is a key pathway in inflammatory regulation, yet the precise mechanistic actions remain elusive. This study aimed to elucidate the mechanism by which LSW regulates sphingolipid metabolism to mitigate influenza-induced inflammatory responses.MethodsThe potential mechanisms of LSW were initially predicted and validated via network pharmacology and lipidomics. A549 cells were infected with influenza A/Puerto Rico/8/34 (H1N1) (PR8) or transfected to overexpress sphingosine kinase-1 (SPHK1), then treated with LSW. In vivo, mice were infected with PR8 or challenged with rAAV9-SPHK1 and administered LSW for 5 days. Inflammatory factors and sphingolipid pathway-associated proteins were evaluated.ResultsNetwork pharmacology identified sphingolipid signaling as a primary target of LSW. Lipidomics revealed LSW significantly reduced the levels of sphingomyelin (SM), ceramide, CerG2GNAc1, CerG3GNAc1, Ceramide phosphate and GM1 in lungs. In PR8-infected A549 cells, LSW significantly reduced sphingomyelinase (ASMase) and Ceramide (Cer) secretion. It also inhibited the expression of SPHK1 and sphingosine-1-phosphate (S1P) in A549 cells and in mice. Pharmacological inhibition of SPHK1 mirrored these anti-inflammatory effects. In SPHK1-overexpressing or TNF-α-stimulated A549 cells, LSW significantly attenuated the expression of SPHK1, CXCL10, and MCP-1. In the rAAV9-SPHK1 overexpression mouse model, LSW ameliorated lung pathological changes and reduced the expression of SPHK1, IFN-γ, and TNF-α.ConclusionLSW alleviates influenza virus-induced inflammation by inhibiting the overactivation of the sphingolipid signaling pathway, specifically through targeting the SPHK1-S1P axis and ceramide-derived lipid mediators.